Synthesis, Characterization of Novel Azo Compounds as Corrosion Inhibitors for Carbon Steel in HCl, and Their Theoretical Study - Jarallah, Hanadi M.; Dhaef, Hawraa Kareem; Mohammed, Mohammed K.; Ismal, Sadiq M. H.; Hussein, Ala’a Ali (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Two azo compounds were produced, and their chemical properties were validated using spectroscopic methods (mass and 1H NMR). A potential dynamic polarization approach was employed to evaluate the synthesized derivatives as corrosionreducing materials for carbon steel in a 1 M HCl solution. The derived products, (E)-4-((3-(tert-butyl)-2-hydroxy-5-methoxyphenyl)diazenyl)-N-(5-methylisoxazol-3-yl)benzenesulfonamide (I) and (E)-4-((2-hydroxynaphthalen-1-yl)diazenyl)-N-(5-methylisoxazol-3-yl)benzenesulfonamide (II) achieved 89.9% and 83.02% inhibition rates at 5 × 10−3 M concentrations, Langmuir was aligned with the isotherm adsorptions of these materials. Density functional theory was employed to assess the quantum chemical characteristics of azo-based inhibitors. A conceptual assessment was performed using DFT/B3LYP 6-311+G (d,p) to evaluate the structure of the molecule, its physical and chemical properties, and the electronic factors that impact its inhibitory significance. The DFT outcomes were aligned with the practical records.